The consequences of uncertainty: Climate sensitivity and economic sensitivity to the climate - John Hassler; Per Krusell; Conny Olovsson (Sveriges Riksbank, 2019)
We construct an integrated assessment model with multiple energy sources - two fossil fuels and "green energy" - and use it to evaluate ranges of plausible estimates for the climate sensitivity as well as for the sensitivity of the economy to climate change. Rather than focusing on uncertainty explicitly, we look at extreme scenarios defined by the upper and lower limits given in available studies in the literature. We compare optimal policy with laissez faire and we point to the possible policy errors that could arise. By far the largest policy error arises when the climate policy is "overly passive"; "overly zealous" climate policy (i.e., a high carbon tax applied when climate change and its negative on the economy are very limited) does not hurt the economy much as there is considerable substitutability between fossil and non-fossil energy sources.
Keywords: 330; Climate change; integrated assessment model; uncertainty